Phase formation, microstructure and magnetic properties of (1-x)BiFeO3-x(0.9Pb(Mg1/3Nb2/3)O3-0. 1PbTiO3) system - Rewadee Wongmaneerung (2018)
Multiferroic composites containing bismuth ferrite (BF) and lead magnesium niobate-lead titanate (0.9PMN-0.1PT) phases were fabricated by solid-state reaction, with 10-50 wt% of 0.9PMN-0.1PT. The phase formation behavior and microstructural features were investigated by X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. Information on the oxidation state of Fe ions was determined by the synchrotron X-rays absorption near edge structure (XANES) technique. A vibrating sample magnetometer (VSM) was used to characterize the magnetic properties. The results indicated that all composites showed a perovskite structure and the PMN-PT phase was compatible with the BF phase. The microstructure displayed mixed BF, PMN and PT phases. In addition, the presence of secondary phases (Bi 2 Fe 4 O 9 and Fe 2 O 3 ) was observed by both XRD and XANES techniques. The presence of BF, Bi 2 Fe 4 O 9 and Fe 2 O 3 phases was also confirmed by the oxidation state and the local structure surrounding the Fe absorbing atom, as observed in the Fe K-edge XANES spectrum. Moreover, the composites exhibited typical magnetic hysteresis (M-H) loops at room temperature. The maximum saturation magnetization (M S ) was observed for x=30 and 40 wt%. © 2013 Elsevier Ltd and Techna Group S.r.l.